Learning Organization At Madrasa Aliyah Negeri (Public Islamic Senior High School) Of Tulungagung Regency, East Java Province (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study was conducted at MAN 1 and MAN 3, Tulungagung Regency, East Java Province in the field of research and robotics which aims to develop a better Islamic civilization and generate a more advanced Islamic education civilization. This study is field research carried out using a qualitative approach. Observation, interviews, and documentation were used to gather data in this study. The study was conducted at MAN 1 and MAN 3, Tulungagung Regency, East Java Province. The formulation of a vision for Islamic senior high schools (MAN) in Tulungagung Regency, East Java Province, is involving all stakeholders and is carried out by looking at the existing opportunities and challenges. Headmaster or school principal of madrasa (Islamic school) who is visionary to be a professional trainer in order is needed to be able to develop the professionalism of the people he leads through various education and training programs and creates a "tough" culture. The personal personality model at Islamic senior high schools in Tulungagung Regency implement human relations, fosters a sense of kinship and unity, builds the enthusiasm of the educational staff to carry out their duties, and develops their academic potential. The common vision of Islamic senior high schools (MAN) in Tulungagung Regency is to build a madrasa atmosphere to foster consistency in the practice of realizing the vision and being informed to teamwork through the madrasa organizational structure. Implementation of tam learning at Islamic senior high schools (MAN) in Tulungagung Regency by collaborating with various institutions and realizing the vision into several prioritized or superior programs. The recommendation for the spirit of the Learning Organization at Madrasa Aliyah makes sincere deeds a spirit that can transcend the boundaries of time and space. "Sincere deeds" are required to be instilled in the mindset and the inner heart as well as to be manifested in the attitude, behavior, and culture of the madrasa.